Pelatihan Peningkatan Kualitas Produk dan Pemasaran Usaha Bubuk Biji Salak di Desa Sungai Langka, Kabupaten Pesawaran - Kiagus Andi; Fitra Dharma; Rindu Rika Gamayuni (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This activity aimed to increase the knowledge and skills of participants in improving the quality of salak seed powder drink products and increasing their marketing. This training is aimed at villagers who drive the salak seed powder business, namely the Dusun 5 Women Farmers Group (KWT), Sungai Langka Village, Gedong Tataan District, Pesawaran Regency, Lampung. Method: The service methods were carried out through surveys, training and mentoring and evaluation. Results: To increase its marketing, FEB Unila's staff have created more attractive product labels that attract more products to sell; besides, they also buy better sealer machines to improve the quality of product packaging. Conclusion: Product quality, production and sales and marketing of salak seed powder must be improved as a solution to the problem so that the villagers' economy will improve.